A New Near‐Infrared Long Persistent Luminescence Material with Its Outstanding Persistent Luminescence Performance and Promising Multifunctional Application Prospects. Issue 18 (15th June 2020) - Ding, Songsong; Guo, Haijie; Feng, Peng; Ye, Qiangfei; Wang, Yuhua
Abstract: In this work, a novel near‐infrared (NIR) persistent luminescence (PersL) material Na2 CaGe5 SiO14 (NCGSO):Cr 3+ is designed and prepared. The phase composition and crystal structure are analyzed by X‐ray diffraction (XRD) and Rietveld structural refinement. The band gap of NCGSO is calculated to be 4.245 eV by density functional theory (DFT) and confirmed by diffuse reflection spectroscopy (DRS). It is determined by the photoluminescence (PL) spectra, X‐ray absorption near‐edge spectroscopy (XANES), and time‐resolved emission spectra (TRES) that three Ge 4+ sites can be superseded simultaneously when Cr 3+ ions are doped. In addition, the PL, photoluminescence excitation (PLE), and PersL performance are analyzed systematically. Under the radiation of 254 nm ultraviolet (UV) lamp, the samples exhibit excellent PL and PersL performance in the range of 600–900 nm, and the optimal afterglow duration lasts for more than 10 h. According to results, a possible mechanism is proposed to explain the PersL phenomenon. In the end, a set of information encrypted digital labels is designed and biological tissue penetration experiments are performed. The results reveal the potential of NCGSO:Cr 3+ for information encryption and biological imaging applications. Abstract : A new long persistent luminescent material Na2 CaGe5 SiO14 :Cr 3+ is reported, and it exhibits excellent optical characteristics in the NIR region, the afterglow duration can reach more than 10 h. Several digital labels for information encryption are designed and biological tissue penetration experiments are performed, the results show that Na2 CaGe5 SiO14 :Cr 3+ has high application potential in information encryption and biological imaging.